Coordinated control of TCSC and UPFC to aid damping oscillations in the power system. Issue 12 (2nd December 2019) - Kumar, Harish; Singh, Ravindra Pratap
ABSTRACT: A valid damping of oscillations is an upcoming extensive challenge while maintaining the stability of the power system. This oscillation generally occurs due to the fluctuation raised, when two systems are interconnected. This paper addresses the oscillation occurred in the power system as the main challenge, which thus performs an effective simulation in 68-bus system. Here, it promotes a sufficient CC with two FACTS devices such as TCSC and UPFC, which are connected with PSS. Further, it adopts firefly algorithm to enable the CC among the FACTS devices. To the next of the simulation, this paper compares the performance of the FF- CC with conventional optimisations include GSO, PSO, GA and ABC algorithms to enable CC. Further, it provides a detailed analysis of the impact of PSS and loading effects on CC. As a result, the performance of FF-CC hands over the stable power system with powerful damping of oscillations, after comparing it with the existing methods. Abbreviations: ABC, Artificial Bee Colony; ICA, Imperialist Competitive Algorithm; AVR, Automatic Voltage Regulators; NETS, New England test system; BFOA, Bacteria Foraging Optimization Algorithm; NYPS, New York power system; BSO, Bacterial Swarm Optimization; PSO, Particle Swarm Optimization; CC, Coordinated Control; PSS, Power System Stabilizers; COA, Chaotic Optimization Algorithm; STATCOM, Static Synchronous Compensator; CS, Cuckoo Search; SSSC, Static Synchronous Series Compensator; FACTS, Flexible Alternating Current Transmission System; SVC, Static Var Compensator; GA, Genetic Algorithm; TCSC, Thyristor Controlled Series Capacitor; GSO, Gravitational Search Algorithm; UPFC, Unified Power Flow Controller